KARAKTERISASI REPRODUKSI DAN NILAI HETEROSIS HASIL PERSILANGAN IKAN GURAME BASTAR DAN BLUESAFIR - Deni Radona; Nunak Nafiqoh (Research Center for Biology-Indonesian Institute of Sciences, 2014)
Hybridization is one alternative of genetic improvement to increase the production of commercialize commodity. The aim of this study was to determine the character of reproductive performance and the value of heterosis from cross-breeding of giant gouramy (Osphronemus gouramy) strain Bastar and Bluesafir. Crosses were performed in both directions (reciprocal) with naturally spawning system. Two pairs of giant gouramy of each strain were used, each pair contained 4 ? and 1 ?. Every pairs were reared in 3 x 3 m of pond.Reproductive characterization, such as Fecundity, Ovo Somatic Index, egg diameter, egg weight, Fertilization Rate (FR), Hatching Rate (HR), the latency time of hatching, and yolk sack absorbtion period, were observed. Other parameters including larval lenght and Survival Rate (SR) were also observed. Heterosis (H) value was calculated from FR, HR and SR. Result showed that each population and its cross-breed had no different in reproductive characters. Latency time of hatching, egg diameter, egg weight and yolk sac absorbtion period values were 3 ± 0 days; 0.74 ± 0.05 cm; 11 ± 4 mg dan 9 ± 1 days, respectively. Meanwhile fecundity value showed that Blusafir strain had higher fecundity (3661 ± 624), and Ovo Somatic Index percentage (21.96 ± 3.74). The highest HR was presented by ? Bluesafir x ? Bastar (97.95 ± 0.47 %), meanwhile ? Bastar x ? Bluesafir presented the highest FR and SR (99.15 ± 0.34 % and 92.57 ± 0.40 %). Heterosis value showed that cross-breeding between ? Bastar x ? Bluesafir had better HR and SR (1.20 and 2.37), white hand cross-breeding between ? Bluesafir x ? Bastar presented better FR (0.69).